The Relationship between Understanding of Married Couple toward Premarital Course Topic by Behavior Family at X Koto Singkarak Subdistrict Solok Regency - Zulfikri Syarif; Setiawati Setiawati (Universitas Negeri Padang, 2020)
This research is motivated by the increase in divorce rates in District X of Koto Singkarak in the last three years, namely in 2017 there were 72 divorce cases, 2018 there were 76 divorce cases, and in 2019 there were 114 cases. The increase in divorce rates is due to the lack of good behavior of married couples, while the married couples have joined the pre-marital course program. This is allegedly due to the low understanding of married couples towards the pre-marital course topic. This study aims to look at the description of the understanding of married couples on pre-marital course topics, see the behavior of married couples in families, and see the relationship between the two. This type of research is correlational with a quantitative approach. The population in this study were 200 married couples who had received pre-marital courses and were still domiciled in District X of Koto Singkarak. The sampling technique is Probability Sampling type Convenient Sampling. Samples were taken as many as 40 people. Data collection techniques using a questionnaire technique with a questionnaire. Data analysis techniques the percentage formula. The results showed that: (1) The understanding of married couples about pre-marital course material is very high; (2) The behavior of married couples in married life is classified as bad; (3) There is no relationship between the understanding of husband and wife to pre-marital course topic with behavior in the family.Keywords: Retention of Topic, Pre-Marital Course, Family Behavior